The Effect of Magnesium Supplementation on EMG Indices of Muscle Fatigue Followed by Acute Anaerobic Exercise - Zia Falah Mohammadi; Vahid Talebi; Normohammad Delavari Banitak; Abazar Shirazi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2018)
Background and Objectives: Magnesium is a cofactor with more than 300 enzymes, which affect energy production and the nervous system. This research aimed to investigate the effect of magnesium intake on musculoskeletal fatigue electromyography indices following intense anaerobic exercise.   Methods: Sixteen active male students voluntarily participated in this semi-experimental study. The subjects were randomly divided into two groups of supplement and placebo. EMG electrodes were placed on muscles based on SENIAM instructions. Test was performed on a bicycle ergometer (lode, Netherland) and at the same time, the right leg muscles activity, was recorded using an EMG device. Data were analyzed by paired and independent t-tests. The significance level was considered to be 0.05.   Results: Magnesium supplementation reduces intragroup RMS of vastus medialis, vastus lateralis, and gastrocnemius lateralis muscles (p=0.001, p=0.05, p=0.001, respectively), but between-group values had no significant difference. Magnesium intake also increased MPF in vastus medialis, vastus lateralis, and gastrocnemius lateralis muscles (p=0.001, p=0.05, p=0.05, respectively), and also between-group comparison showed increase in vastus lateralis in supplement group (p=0.026).   Conclusion: Based on the findings of this study, magnesium sulfate supplementation improves the performance of healthy active subjects in a short period of intense activity, such as Wingate test.